Real-Time Video Latency Measurement between a Robot and Its Remote Control Station: Causes and Mitigation. (2nd December 2018) - Kaknjo, Admir; Rao, Muzaffar; Omerdic, Edin; Robinson, Luke; Toal, Daniel; Newe, Thomas
Abstract : This work presents a detailed study, characterization, and measurement of video latency in a real-time video streaming application. The target application consists of an automatic control system in the form of a control station and the mini Remotely Operated Vehicle (ROV) equipped with a camera, which is controllable over local area network (LAN) and the Internet. Control signal transmission and feedback measurements to the operator usually impose real-time constraints on the network channel. Similarly, the video stream, which is required for the normal system control and maneuvering, imposes further strict requirements on the network in terms of bandwidth and latency. Based on these requirements, controlling the system in real time through a standard Internet connection is a challenging task. The measurement of important network parameters like availability, bandwidth, and latency has become mandatory for remotely controlling the system in real time. It is necessary to establish a methodology for the measurement of video and network latency to improve the real-time controllability and safety of the system as such measurement is not possible using existing solutions due to the following reasons: insufficient accuracy, relying on the Internet resources such as generic Network Time Protocol (NTP) servers, inability to obtain one-way delay measurement, and many solutions only having support for web cameras. Here, an efficient, reliable, and cost-effective methodology for the measurement of latency of a video stream over a LAN and the Internet is proposed. A dedicated stratum-1 NTP server is used and the necessary software needed for acquiring and measuring the latency of a video stream from a generic IP camera as well as integration into the existing ROV control software was developed. Here, by using the software and dedicated clock synchronization equipment (NTP server), it was found that normal video latencies in a LAN were in the range of 488ms – 850ms, while latencies over the Internet were measured to be in the range of 558ms – 1211ms. It is important to note that the values were obtained by using a generic (off-the-shelf) IP camera and they represent the actual latencies which might be experienced during control over long range and across international territory borders.